Through time and space with Benedict Breadfruit - Garrett, Randall, 1927-1987 (Salt Lake City, UT : Project Gutenberg, 2023)
"Through Time and Space With Benedict Breadfruit" by Grandall Barretton is a science fiction collection of short stories written during the early 1960s. The book follows the titular character, Benedict Breadfruit, as he navigates various interplanetary adventures, interacting with unique alien species and exploring the peculiarities of their worlds. The stories blend humor and imagination, showcasing a playful take on science fiction tropes. In this collection, Benedict Breadfruit is portrayed as a resourceful and witty protagonist confronting extraordinary challenges across different planets. The stories cover diverse scenarios, including saving a dying intelligent lichen on Phogiu II, using unconventional methods to deal with space pests, and navigating peculiar cultural practices on alien worlds. Each tale brings forth a mix of humor and satire, as Breadfruit's interactions reveal the absurdities of both alien societies and human perceptions, ultimately celebrating the whimsical nature of existence within the universe. (This is an automatically generated summary.)
Consists of a series of feghoots, or shaggy dog stories, featuring puns on the names of sci-fi authors of the time. Feghoots at Wikipedia: https://en.wikipedia.org/wiki/Feghoot
Release date is 2023-11-28
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; American wit and humor; Puns and punning; Shaggy dog stories